PEMBATALAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) AKIBAT PANDEMI COVID 19 (Lex Jurnalica, 2022)
ABSTRACTBuyers (consumers) who are affected by COVID-19 and have been bound by a house sale and purchase binding agreement have the potential to experience losses when canceling the agreement. Whereas the buyer is aware that if the agreement is continued, there will be a potential for default due to the buyer's financial condition. This research is a juridical normative research. The formulation of the problem in this research is whether covid 19 can be used as a reason to cancel the Sale and Purchase Binding Agreement (PPJB) and what legal remedies the buyer can take when the credit application is rejected by the bank. The results of the analysis show that the Covid-19 Pandemic can be used as a reason to change the contents or cancel the Sale and Purchase Binding Agreement (PPJB), but this cannot be done immediately but through a renegotiation mechanism to change the contents or cancel the agreement. Efforts that can be made by the buyer when the credit application is rejected by the bank is to ask for a refund that has been paid according to the provisions of the applicable legislation.Keywords: Sale and Purchase Binding Agreement, Covid 19 Pandemic.ABSTRAKPembeli (konsumen) yang terdampak covid 19 dan telah terikat dengan perjanjian pengikatan jual beli rumah berpotensi mengalami kerugian ketika akan membatalkan perjanjian. Padahal pembeli menyadari bahwa jika perjanjian dilanjutkan akan berpotensi terjadi wanprestasi akibat kondisi keuangan pembeli. Penelitian ini adalah penelitian normatif yuridis. Rumusan masalah dalam penelitian ini adalah apakah covid 19 dapat dijadikan alasan untuk membatalkan Perjanjian Pengikatan Jual Beli (PPJB) dan upaya hukum apa yang dapat dilakukan pembeli ketika permohonan kredit ditolak oleh perbankan. Hasil analisis menunjukan bahwa Pandemi Covid-19 dapat dijadikan alasan untuk mengubah isi atau membatalkan Perjanjian Pengikatan Jual Beli (PPJB), namun hal ini tidak bisa dilakukan seketika melainkan melalui mekanisme renegosiasi untuk mengubah isi atau membatalkan perjanjian. Upaya yang dapat dilakukan pembeli ketika permohonan kredit ditolak oleh perbankan adalah meminta pengembalian uang telah dibayarkan sesuai ketentuan perundang-undangan yang berlaku.Kata Kunci: Perjanjian Pengikatan Jual Beli, Pandemi Covid-19.